2018
DOI: 10.1371/journal.pone.0193560
|View full text |Cite
|
Sign up to set email alerts
|

Arylamine N-acetyltransferase 1 protects against reactive oxygen species during glucose starvation: Role in the regulation of p53 stability

Abstract: Human arylamine N-acetyltransferase 1 (NAT1) has been associated with cancer cell growth and invasion, but the underlying molecular mechanisms remain unknown. NAT1 is located on the short arm of chromosome 8 (8p21), a region that is commonly deleted in colon cancer. Previously, it was reported that HT-29 colon cancer cells, which have a large deletion at 8p21-22, show marked morphological changes, increased E-cadherin expression and altered cell-cell contact inhibition following down-regulation of NAT1 with sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Previously, we reported that deletion of NAT1 in various human cells including MDA-MB-231 cells, using CRISPR/Cas9 technology decreased oxidative phosphorylation (Lichter et al, 2017). Moreover, in human HT-29 cells, glucose utilisation decreased and ROS production increased following NAT1 deletion (Wang et al, 2018). These studies suggested that NAT1 affected mitochondrial function in a similar manner to that seen following Nat1 knockdown in mice.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Previously, we reported that deletion of NAT1 in various human cells including MDA-MB-231 cells, using CRISPR/Cas9 technology decreased oxidative phosphorylation (Lichter et al, 2017). Moreover, in human HT-29 cells, glucose utilisation decreased and ROS production increased following NAT1 deletion (Wang et al, 2018). These studies suggested that NAT1 affected mitochondrial function in a similar manner to that seen following Nat1 knockdown in mice.…”
Section: Introductionmentioning
confidence: 67%
“…However, this was not seen in BT-549 cells (Tiang et al, 2015). Deletion of the NAT1 gene increased reactive oxygen (ROS) production and apoptosis, especially under nutrient stress, in HT-29 cells but not in HeLa cells (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NAT1 gene was disrupted using CRISPR/Cas9 system as previously described [37]. After selection with puromycin (5 µM), single colonies were selected, expanded, and NAT1 activities measured by a highperformance liquid chromatography assay to screen for the NAT1 knockout cell lines [38].…”
Section: Generation Of Nat1 Crispr/cas9 Knockout Cell Linesmentioning
confidence: 99%